ANALISIS PERSEPSI STAKEHOLDER TERKAIT IMPLEMENTASI KAWASAN EKONOMI KHUSUS (KEK) VERSUS FREE TRADE ZONE (FTZ) DI KOTA BATAM - Rikson Pandapotan Tampubolon (Universitas Putera Batam, 2018)
This study aims to evaluate the free trade zone system that has been carried out with the planned implementation of special economic zones in Batam City. The economic downturn in the city of Batam has made stakeholders think again about the concept of free trade zone (ftz) or Free Port and Free Trade Zone. The FTZ concept is deemed no longer compatible with the current flow and competitiveness of change. For this reason, the central government offers the concept of special economic zones (KEK) to revive the passion of economic growth in this Industrial City. However, in the implementation there were many criticisms made by the community, especially businessmen who considered SEZ not to answer the problems that exist in Batam's economic growth. This study uses a qualitative approach to see each perception from stakeholders (stakeholders) to be a consideration in making decisions. Based on the results of the analysis, it was found that it was important that all stakeholders would sit together to discuss the good about the economy. The government must prioritize a bottom-up approach to find solutions to problems regarding the polemic of the best economic system problems for Batam City.